2018
DOI: 10.1093/ips/oly029
|View full text |Cite
|
Sign up to set email alerts
|

In the Shadow of Asylum Decision-Making: The Knowledge Politics of Country-of-Origin Information

Abstract: Country-of-origin information has secured a central place in European asylum systems, underpinning state decisions on the asylum status of refugee populations. All European states produce this type of information, and dedicated country-of-origin information units are increasingly common. This article analyzes the knowledge politics of countryof-origin information, with a focus on the relation between knowledge and decision. We are interested in this type of knowledge precisely because it is uneasily positioned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…If we return to the topic of this article, the mimetic tradition in human geography, in which maps are seen as relatively accurate representations of reality, fits with the description of country information as a “collection of objective facts allowing rational and de-politicised decision-making” (Rosset 2019, 109). The units that produce and compile country information for the purpose of asylum assessments tend to emphasize that the presentation of objective facts is the goal of their knowledge production (van der Kist, Dijstelbloem, and Goede 2019). The mimetic approach to knowledge resembles, moreover, the positivist view of facts frequently found in legal discourse (Sweeney 2007, 30).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…If we return to the topic of this article, the mimetic tradition in human geography, in which maps are seen as relatively accurate representations of reality, fits with the description of country information as a “collection of objective facts allowing rational and de-politicised decision-making” (Rosset 2019, 109). The units that produce and compile country information for the purpose of asylum assessments tend to emphasize that the presentation of objective facts is the goal of their knowledge production (van der Kist, Dijstelbloem, and Goede 2019). The mimetic approach to knowledge resembles, moreover, the positivist view of facts frequently found in legal discourse (Sweeney 2007, 30).…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, some scholars have investigated the role of country information in French and British asylum procedures (Gibb and Good 2013) and its use in collaboration and policy-making in the European Union (EU) (Engelmann 2015). Other studies have investigated the production of country information (Rosset and Liodden 2015; Rosset 2019; van der Kist, Djistelbloem, and de Goede 2019), as well as the different ways in which the producers of country information bolster the public legitimacy of such knowledge (van der Kist and Rosset 2020). The most notable scholarly contribution on the topic is Good’s study of anthropologists who act as country experts in asylum cases in UK courts (2007, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…They are developed by a variety of organizations, but primarily by non-profit organizations (for example, the charity Asylos) 2 ; national government agencies (for example, the UK Home Office) 3 ; and regional and international governmental agencies (for example, the European Asylum Support Office (EASO) 4 and UN High Commissioner for Refugees (UNHCR)) (hereinafter, 'COI service providers'). 5 As such, COI reports typically provide detailed information on conditions in countries from which asylum seekers originate (or through which they transit)based on fieldwork and/or desk research (Van der Kist et al 2019)-in order to substantiate claims for asylum in host countries on the basis of, inter alia, refugee and human rights grounds. 6 Notably, for the purposes of seeking asylum as a refugee, it must be demonstrated that the claimant is unable or unwilling to return to their country of origin due to a 'well-founded fear of being persecuted for reasons of race, religion, nationality, membership of a particular social group or political opinion'.…”
Section: Introductionmentioning
confidence: 99%
“…See for example the 'Eritrea Controversy' (the 2014 decision of the Danish authorities to suspend refugee status determination for Eritrean asylum seekers, and subsequent volte-face, was based on a politicized COI report produced by the Danish Immigration Service as part of a strategic effort to pursue restrictive asylum policies) (van derKist et al 2019).10 See Art 16(1) of the EU Asylum Procedures Directive 2005 (n 6), and ACCORD (2013), Principle 2.2.2 (p 37). 11 See n 7 and Asylos and Haagsma, J.…”
mentioning
confidence: 99%
See 1 more Smart Citation